Study of the Seismic Behavior of Tunnels in the Closed Excavation Phase - سليطين, إياد (Latakia University Journal -Engineering Sciences Series, 2024)
This paper presents a 3D numerical analysis of the influence of the excavation process on the soil-tunnel interaction under seismic loading. This issue requires a non linear analysis since the excavation procedure induces a perturbation in the stress distribution adjacent to the tunnel lining. Numerical analyses are conducted for both shallow and deep tunnel embedded in soft soils and under different seismic amplitudes. Results show that for shallow tunnel the excavation process has a significant influence on the overall seismic response of the soil-tunnel system.